2022
DOI: 10.1183/13993003.01596-2022
|View full text |Cite
|
Sign up to set email alerts
|

Global estimates and determinants of antituberculosis drug pharmacokinetics in children and adolescents: a systematic review and individual patient data meta-analysis

Abstract: BackgroundSuboptimal exposure to antituberculosis drugs has been associated with unfavourable treatment outcomes. We aimed to investigate estimates and determinants of first-line antituberculosis drug pharmacokinetics in children and adolescents at a global level.MethodsWe systematically searched MEDLINE, Embase, and Web of Science (1990–2021) for pharmacokinetic studies of first-line antituberculosis drugs in children and adolescents. Individual patient data were obtained from authors of eligible studies. Sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Dose in mg/kg is known to be an important determinant of isoniazid exposure. 32 In a previous modelling study among MDR-TB patients in South Africa, isoniazid at higher doses was found to exhibit non-linear PK. 16 In the current study, however, doses were not found to be significantly associated with isoniazid exposures.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dose in mg/kg is known to be an important determinant of isoniazid exposure. 32 In a previous modelling study among MDR-TB patients in South Africa, isoniazid at higher doses was found to exhibit non-linear PK. 16 In the current study, however, doses were not found to be significantly associated with isoniazid exposures.…”
Section: Discussionmentioning
confidence: 94%
“…This might be explained by the small range of mg/kg doses used in the study (IQR 10.4–11.9 mg/kg), which may have obscured the true relationship. Aside from dose in mg/kg, acetylator status based on N -acetyltransferase 2 genotypes or other phenotyping methods has been described as a strong determinant of isoniazid exposure, either in DS-TB patients 32 , 33 or in MDR-TB patients. 11 , 16 , 17 As confirmed by our study, acetylator status is indeed an important determinant of isoniazid exposure, with non-slow acetylators showing a 63% decrease in AUC 0–24 compared with slow acetylators.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that young children generally require a longer time for virological suppression after ART initiation, we advise caution when studying OD dosing of dolutegravir in infants on rifampicin-based TB treatment. On top of that, currently recommended dosages of rifampicin have been reported to result in low exposure (AUC) in infants, and higher dosages may therefore be introduced in the near future [ 35 ]. Additionally, studies are exploring the potential use of high-dose rifampicin (up to 35 mg/kg) for children [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This information can serve as a practical leaflet for clinicians [ 12 , 100 ]. Toxicity and PK related to the clinical outcomes of anti-TB drugs are two crucial aspects of TB research, which have been intensively discussed elsewhere [ 10 , 27 , 31 , 54 , 74 , [100] , [101] , [102] , [103] , [104] , [105] , [106] ]. In the study on AEs surveillance, Ngoc et al [ 104 ] discussed that the administration of long regimens of injectable anti-TB drugs could result in the increased risk of AEs.…”
Section: Six Primary Prospects In Tb Clinical Managementmentioning
confidence: 99%